2005
DOI: 10.1016/j.scitotenv.2004.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Sources, distribution and variability of hydrocarbons and metals in atmospheric deposition in an urban area (Paris, France)

Abstract: Total atmospheric deposition, i.e., both wet and dry deposition, was sampled during 11 months in the "Ile-de-France" region, France. Monthly fluxes of aliphatic hydrocarbons (AHs), polycyclic aromatic hydrocarbons (PAHs) and heavy metals (HMs) were studied at three representative sites (two urbanised and one semiurban). A combination of spatial and temporal variability of total fluxes and pollutant fingerprints allows a better understanding of atmospheric pollutant dynamics over this region. In the whole studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(105 citation statements)
references
References 50 publications
(62 reference statements)
5
96
1
3
Order By: Relevance
“…The sources of PAHs, either from petrogenic and pyrolytic origin, may be identified by ratios of specific PAH compounds [43][44][45][46]. A ratio between low molecular weight (LMW), two or three rings, and high molecular weight (HMW), four to six rings, higher than 1, dominates in the petrogenic source [43,44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sources of PAHs, either from petrogenic and pyrolytic origin, may be identified by ratios of specific PAH compounds [43][44][45][46]. A ratio between low molecular weight (LMW), two or three rings, and high molecular weight (HMW), four to six rings, higher than 1, dominates in the petrogenic source [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…A ratio between low molecular weight (LMW), two or three rings, and high molecular weight (HMW), four to six rings, higher than 1, dominates in the petrogenic source [43,44]. Some authors [45,46] also suggested that PAH contamination of a petrogenic origin is characterized by phenanthrene/anthracene (PHE/ANT) ratio N10 and fluorine/pyrene (FL/PYR)b 1, while PHE/ANT ratio b10 and FL/PY N1 have been suggested for pyrolytic sources.…”
Section: Resultsmentioning
confidence: 99%
“…However, the decreasing heavy metal concentrations along the road with increasing distance to the industry show that traffic is not the primary source for the observed heavy metal contamination. In Bucharest, however, traffic might be the most significant source for heavy metals, especially for lead (Azimi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the dominant species for PM 2.5 are sulfate and ammonium (Chio et al, 2004), while the trace elements found are arsenic, copper, zinc, selenium, lead, bromine, vanadium, and sodium, which can be associated with industrial, agricultural, and vehicular sources (Malm et al, 2000). Finally, the heavy metals in the PM are from industrial source which are the main contributes of such materials to the urban atmosphere (Azimi et al, 2005;Zhang, 2009).…”
Section: Introductionmentioning
confidence: 99%